Al-A’ZAMĪ DAN FENOMENA QIRAAT ALQURAN: ANTARA MULTIPLE READING DENGAN VARIANT READING - Khaeruddin Yusuf (State Institute of Islamic Studies (IAIN) Palu, 2014)
Absract: This article discusses one of the phenomena in the sciences of the Quran employing the point of view of the contemporary muslim scholar, Muḥammad Muṣṭāfā al-A’zamī. He asserted that one of the entrances used by the Orientalist to assault the authenticity of the Qur'an was through qiraat phenomenon. Al-A’zamī critisized the Orientalist’s views in terms of methodology, of analysis process and of study results. The nonexistance of a dot and diacriticals did not become a problem for the text of the Koran since the system of the true recitation was taught by the prophet through memorization. The true system of reciting the Qur’an had already existed in the minds of the Companions of the Prophet. The terms used in recitation cannot also be separated from Al-A’zamī’s attention. He said that the term “multiple” (many) recitaions is more properly used than the term “variant” (various) recitations.Kata Kunci: qiraat, multiple qiraat, tanda titik, diakritikal